Real world data on outcomes of anti-CD38 antibody treated, including triple class refractory, patients with multiple myeloma: a multi-institutional report from the Canadian Myeloma Research Group (CMRG) Database - A. Visram; A. De La Torre; D. White; J. Su; E. Masih-Khan; M. Chu; V. Jimenez-Zepeda; A. McCurdy; R. LeBlanc; K. Song; H. Mian; M. Louzada; et al. (Blood Cancer Journal)
Abstract Multiple myeloma (MM) remains incurable despite the availability of novel agents. This multi-center retrospective cohort study used the Canadian Myeloma Research Group Database to describe real-world outcomes of patients withanti-CD38 monoclonal antibody (mAb) refractory MM subsequently treated with standard of care (SoC) regimens. Patients with triple class refractory (TCR) disease (refractory to a proteasome inhibitor, immunomodulatory drug, and anti-CD38 mAb) were examined as a distinct cohort. Overall, 663 patients had disease progression on anti-CD38 mAb therapy, 466 received further treatment (346 with SoC regimens were included, 120 with investigational agents on clinical trial and were excluded). The median age at initiation of subsequent SoC therapy of 67.9 (range 39.6–89.6) years with a median of 3 prior lines (range 1–9). The median PFS and OS from the start of subsequent therapy was 4.6 (95% CI 4.1–5.6) months and 13.3 (95% CI 10.6–16.6) months, respectively. The median PFS and OS of patients with TCR disease (n = 199) was 4.4 (95% CI 3.6–5.3) months and 10.5 (95% CI 8.5–13.8) months. Our results reinforce that real-world patients with relapsed MM, particularly those with TCR disease, have dismal outcomes. There remains an urgent unmet need for the development of and access to effective therapeutics for these patients.